The participatory and sustainable development as social innovation (Research, Society and Development, 2021)
The text presents a brief diagnostic of contemporary society, highlighting the challenges and opportunities confronting the national states. It describes the crisis of modern industrial society and the emergence of a new social order in which the sustainable development becomes a vital issue. To follow reflecting on the concept human development and, from this perspective, considers the participation as the most important aspect of development. The author assumes that the effective participation of individuals and the community is possible through the organization, promotion and improvement of human resources, that is, through an inherently educational process. Educational process what incorporate alternative science and technology for sustainable development in the communities. On the other hand, he explains that the human development can only be performed on the level of social justice that is tailored by making decisions based on consultation. The process of consultation ought to be promoted with the purpose of achieved the effective participation of the individuals as of the communities in decision-making of your own model of development. In conclusion, the author suggests that the acceptance of the concept of world citizenship is the indispensable correlate of this contemporary social process; without this type of global ethic, the people may not become active participants and constructive in worldwide process of sustainable development.